(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This study inspects the psychographic and personal conduct standards of watchers of Hindi web series contents on beyond ridiculous (Over-The-Top) platforms. The investigation centers around grasping the motivations, segment profiles, seeing propensities and the more extensive psychosocial effect of this pattern. This study utilized Biblioshiny, an online bibliometric analysis tool, to examine a number of papers sourced from different databases including the Scopus database. The keywords “psychographics”, “digital consumption” and “web series” will let to identify over-the-top content preferences. This review gives a thorough outline of the developing scene of online content consumption in India, focusing on the language of Hindi. Key discoveries show a transcendent youthful, metropolitan and educated crowd, with unmistakable inclinations and standards of conduct that have huge implications for content makers and advertisers.